STUDI HALUAN KAPAL SELAM BENTUK KAPSUL UNTUK MEMINIMALISIR HAMBATAN GESEK TERHADAP AIR LAUT - Suranto, Purwo Joko; Sulistyawati, Wiwin (Bina Teknika, 2016)
Submarine has been widely used both for military and for underwater research, various models of hull forms including capsule-shaped submarine. From the capsule form is to be modified in order to get bow shape forms the barrier fluid is small, so the use of power the main engine will be smaller and can save fuel. The shape and size of the bow of the submarine models to be analyzed consists of three (3) the shape and size of the different models. Model first (1) shaped like a capsule, the second model (2) measure the same length as the capsule form is only the tip of the bow made a sharp resembles a bullet, the third model (3) the same shape as the second model just the tip of the bow that resembles the size of a bullet extended. Fluid analysis using ANSYS CFD software version 15.0. where modeling and manufacturing of using ICEM CFD meshing, defining domain for the fluid and the boundary layer to limit the fluid domain using CFX-Pre, iteration calculation using CFX Solver Manager while to display the results of calculations using CFD-post. Meshing is used to achieve independent meshing, so if meshing plus will not affect the results obtained. Results Barriers fluid to the model of unity of 294 581 Newton, for the second model of 275 961 Newton while the third model obtained at 271 939 Newton.